Postmodern Humour: Parody and Pastiche in the Post-Soviet Prose of Juozas Erlickas - Kišonaitė, Gabija (Colloquia, 2026)
In the context of the state of research on postmodern and comic literature in Lithuania, the article examines the expression of parody and pastiche, the relationship between them, and the nature of their connections with hypotexts in the Juozas Erlickas’ prose texts of Knyga (1996, second ed. 1998, third ed. 2006) and History of Lithuania (2000). The concepts of parody and pastiche are defined, their relationship is determined based on the works of postmodernist theorists: Linda Hutcheon, Fredric Jameson, Rose A. Margaret, etc. The article examines the nature of the relationship between Erlickas’ texts and works of socialist realism, national Lithuanian, and world literature. The analysis allows to identify that Erlickas’ parody is diffuse, almost in all cases ironic and critical of texts written in the socialist realism method and/or the sociocultural reality of Lithuania. The nature of the relationship with other types of literary hypotexts is usually pastiche. Very often, parody and pastiche intertwine and function on different levels of the same text.